Learning of Spatial Operations in 1st Grade of Junior High School (MTs.S NU Paringgonan) Ulu Barumun Sub-district Padang Lawas Regency - Ahmad Nizar Rangkuti; Wildan Saleh Hasibuan (BIRCU, 2019)
The background of the problem in this study is that many students are confused and do not understand how to operate integers in a positive form with positive, positive with negative, negative with positive, and negative with negative. The formulation of this research problem is how to learn integer operations in 1st grade class (VII-2), how students behave in learning integer operations in 1st grade class (VII-2), and how student learning outcomes in learning integer operations in 1st grade class (VII-2). The purpose of this study was to find out integer operating learning in 1st grade class VII-2, to find out the attitudes of students in learning integer operations in 1st grade class (VII-2), and to find out student learning outcomes in integer operating learning in 1st grade class (VII-2) MTs.S NU Paringgonan Ulu Barumun Sub-district. This research is descriptive qualitative research, namely research intended to investigate the circumstances, conditions or other things that have been mentioned, the results of which are presented in the form of research reports. The data needed are observation, interviews, and documentation. The results of this study are (1) Learning integer operations in 1st grade class (VII-2) that the mathematics teacher in 1st grade class (VII-2) describes integer operations by carrying out preliminary activities, core activities, and closing activities. (2) The attitude of students in learning integer operations in 1st grade class (VII-2) is not good, like many students who pay less attention and respect for the teacher during the learning process. (3) Student learning outcomes reach a value of 50 - 80, namely 30 students who do not complete or 88% and 4 students who complete or 12% with the results of the average value is 60, which is not good.